Effect of different genres of music on behavior and milking parameters of dairy cows during milking - Pinkerton, Madison P.; England, Zachary; Wenner, Benjamin A.; Pempek, Jessica A. (Frontiers in Animal Science, 2025)
Compared to other enrichment modalities, relatively few studies have been conducted to evaluate sensory stimulation as environmental enrichment in dairy cows. The aim of this study was to explore the effect of music played in the milking parlor on the behavior and milking parameters of dairy cows during the afternoon milking. Ninety-one Jersey cows were introduced to one of five music treatments, including no music or classical, country, Latin, rock music genres, in the milking parlor over four 5-day periods in a switchback experiment. One music treatment was applied per day. The amount of milk harvested from the afternoon milking and milking duration were recorded for all cows, and average milk flow rate was calculated. Cow behavior at milking cluster attachment was video recorded and assessed for a subset of cows (n = 38) by scoring flinch, step, or kick (FSK) responses using a 4-point system based on the direction and height of hind leg movements. The amount of milk harvested increased by 0.5, 0.3, 0.4, and 0.2 kg when classical music was played compared to no music, country, Latin, and rock, respectively. Treatment did not influence milking duration, average milk flow rate, or FSK responses. Future research is needed to explore the possible influence of parlor music on aspects of human behavior and preference for music genres. Other aspects of animal behavior (e.g., temperament, total number of FSK responses) should also be considered in future studies, as well as cows’ response to music in other farm environments.